2013
DOI: 10.1039/c3ay26520j
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of multiple bile acids in uninephrectomized rats using ultra-performance liquid chromatography-tandem mass spectrometry

Abstract: In order to study the roles of individual BAs and due to limited blood sample volumes available from experimental animals, improved methods for the simultaneous quantification of multiple BAs are needed. We developed and validated an ultra-performance liquid chromatography tandem mass spectrometry (UPLC-MS/MS) method for the quantification of 24 BAs, including 11 unconjugated, 6 glycine-conjugated and 7 taurine-conjugated BAs, in 50 mL of rat serum or plasma. The UPLC-MS/MS method, operated in negative and pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 39 publications
0
24
0
Order By: Relevance
“…Since we had previously shown increases in bile salts following UniNX, we chose to investigate whether bile salt receptor FXR (Penno et al, 2013 ; Gai et al, 2014a ) and its potential regulator SIRT1 (Garcia-Rodriguez et al, 2014 ) were altered in various tissues. Here we show that both were modified in tissues by UniNX.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since we had previously shown increases in bile salts following UniNX, we chose to investigate whether bile salt receptor FXR (Penno et al, 2013 ; Gai et al, 2014a ) and its potential regulator SIRT1 (Garcia-Rodriguez et al, 2014 ) were altered in various tissues. Here we show that both were modified in tissues by UniNX.…”
Section: Discussionmentioning
confidence: 99%
“…Activation of SIRT1 and FXR can counter the metabolic syndrome by acting on lipid and glucose metabolism. We and others have recently shown that bile salts and their receptor FXR are modified by UniNX (Penno et al, 2013 ; Gai et al, 2014a , b ; Chin et al, 2015 ). It has also been reported that SIRT1 may regulate FXR activity (Liu et al, 2014 ).…”
Section: Introductionmentioning
confidence: 98%
“…Plasma total cholesterol and creatinine concentrations were measured using a synchro CX3 autoanalyzer (Beckman Instruments). Plasma total bile acids were measured using a kit from Crystal Chemistry, and individual bile acid species were quantitated by liquid chromatography-tandem mass spectrometry (LC-MS/MS) (27). Urinary protein concentrations were determined using a kit from Wako Chemical Industries (Tokyo, Japan).…”
Section: Methodsmentioning
confidence: 99%
“…Concomitantly, lysates were used in parallel experiments to assess the conversion of cortisone to cortisol. Reaction products were directly measured by mass spectrometry as described previously ( 26,31 ). The rate of all reactions was kept below 25% of substrate conversion, with the exception of the comparison of product formation from 7-oxoLCA shown in Fig.…”
Section: Reduction Of 7-oxolca By Recombinant 11 ␤ -Hsd1 From Variousmentioning
confidence: 99%
“…Extraction and quantifi cation of bile acids in plasma samples was performed essentially as described previously ( 31 ). The extraction of bile acids from liver tissue was performed by homogenizing 100 mg of tissue in 200 µl 50% methanol.…”
Section: Quantifi Cation Of 7-oxolca and Its Taurine And Glycine Conjmentioning
confidence: 99%